PEMBUATAN BIOBRIKET DARI PELEPAH DAN CANGKANG KELAPA SAWIT: PENGARUH VARIASI KOMPOSISI BAHAN BAKU DAN WAKTU KARBONISASI TERHADAP KUALITAS BRIKET - Iriany, Cindy Carnella, Cici Novita Sari (Jurnal Teknik Kimia USU, 2016)
Briquette was a product of the compaction process of biomass residue used as fuel and it is formed using binder. Briquette from biomass has a high heating value. The quality of briquettes influenced by raw material composition and the time of carbonization. The carbonization process in the manufacture of briquettes could improve heating value and reduce smoke produced from burning briquette. This research is aim to study the effect of variations in the composition of raw materials and carbonization time on the heating value and the characteristics of the resulting briquettes. The materials used are palm fronds, palm shells, starch, used oil, H2SO4 and Tri Ethyl Amine (TEA). The ratios of palm frond and palm shell charcoal in this research is 1: 2, 1: 4, 1: 6 and 1: 8 with variation of carbonization time 30 minutes, 60 minutes, 90 minutes and 120 minutes. The research began with the carbonization process of the raw materials. Then charcoal product of carbonization was pressed using an binder starch and used oil as much as 20% based on the weight of raw materials at the ratio of 1: 1. The best quality from this research is obtained at the ratio palm fronds and oil palm shell 1: 8 with carbonization time of 120 minutes, heating value 15107,138 cal/g, moisture content 6%, ash content of 5,185%, volatile matter 39,226%, fixed carbon 70,955%, density 0,442 g/cm3, burning rate 0,273 g/min, and compressive strength 0,046 N / mm2. The result shows the briquettes produced had a strong structure, it was not easily broken and it was not moldy when stored.